(untitled) (Bangladesh Journal of Physics, 2024)
The undoped and Cu doped ZnO (Cu: ZnO) nanostructures were successfully synthesized by the chemical bath deposition (CBD) technique to study the influence of copper (Cu) content on its surface morphology, elemental, optical and thermal properties. Powder X-ray diffraction (XRD), Field Emission Scanning electron microscopy (FESEM), energy dispersive X-ray spectroscopy (EDX), ultraviolet-visible (UV-vis) spectroscopy, Thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC) techniques have been used for different characterization. XRD studies showed hexagonal wurtzite ZnO nanostructures, The FESEM analysis revealed that the shape of the undoped ZnO were flower-like structures and the addition of Cu content influenced the morphology of the samples The flower-like structures were changed into a mixed structure with 6 wt% Cu concentration. Interestingly, the flower-like nanostructures were reproduced with smaller grain sizes for 9 wt% Cu content. The EDX results confirmed the presence of Zinc (Zn) and Oxygen (O)and Copper (Cu). In the UV–visible study, the highest band gap energy is obtained for undoped ZnO. The estimated band gap energy was found within the range of (2.95-1.48) eV. The DSC spectra of undoped ZnO displayed an endothermic peak around 211 ℃ whereas a representative 6 wt% Cu Doped ZnO displayed two endothermic peaks around 147 ℃ and 199 ℃. Bangladesh Journal of Physics, Vol. 31, Issue 2, pp. 75 – 81, December 2024